Recalcitrant folliculitis decalvans treated with baricitinib or upadacitinib: a case series - Miguel Antonio Lasheras-Pérez; Rodolfo David Palacios-Diaz; Alejandro Lobato-Berezo; Ricardo Ruiz-Villaverde; Rocío Gil-Redondo; Conrad Pujol-Marco; Mercedes Rodríguez-Serna; Antonio Sahuquillo-Torralba; Kristen I Lo Sicco; Jerry Shapiro; David Saceda-Corralo; Botella-Estrada Rafael (Clinical and Experimental Dermatology, 2026)
A multicenter retrospective study of eleven patients with folliculitis decalvans treated with oral JAK inhibitors (baricitinib or upadacitinib) is reported. Disease stabilization, together with reductions in pustules, crusts, perifollicular erythema, and perifollicular hyperkeratosis, was observed following treatment.